A study on taxpayers' awareness and confidence in administering self assessment / Ho Juan Keng ... [et al.] - Ho, Juan Keng; Sapari, Afidah; Othman, Rani Diana; Loo, Ern Chen (Institute of Research, Development and Commercialization (IRDC), 2005)
Most taxpayers know the differences between the Official Assessment System (GAS) and the Self Assessment System (SAS) and that for individual taxpayers; the GAS has been replaced by the SAS effective from 2004. Although most taxpayers agreed that both the taxpayers and the tax officers should be knowledgeable in assessing tax liabilities, however they felt that the IRB should be responsible for conducting the assessment as taxpayers are not confident in filling their assessments correctly. They lack confidence in understanding the tax laws and public rulings, and in keeping up to date with the frequent changes to the tax laws. Under the GAS, more taxpayers file their own tax returns as compared to under the SAS. Taxpayers are not confident that the tax authority would advise them regarding unintentionally committed errors, nor would the tax authority treat the community as honest taxpayers. They feel the laws that give IRB six years to review an assessment but only 30 days for the taxpayers to appeal against an assessment as unreasonable.